Comparative Acute Toxicity of the Commercial Herbicides Glyphosate to Neotropical Tadpoles Scinax nasicus (ANURA:HYLIDAE) - Lajmanovich, Rafael Carlos (2003)
We investigated the effect of glyphosate (GLY) to Scinax nasicus taoles and the influence of GLY degradation in the variations of LC50 values. These results showed that 96h LC50 for nasicus tadpoles exposed to continuous applications of GLY in reneval test (RT) was 3.13 mg GLY/L compared to an estimated LC50 in static test (ST) of 5.27 mg GLY/L. These data indicate large diferences in toxicity between R.T and S.T nasicus tad poles did no die whwn the GLY esposure was not continous.